Development of Interactive Multimedia Learning Media on Alternative Energy to Improve the Understanding of 3rd Grade Elementary School Students - Iqbal Hadziqi Sumarwi; Suryanti; Zainul Arifin Imam Supardi (Indonesia Approach Education, 2023)
The purpose of this study was to describe the validity, practicality, and effectiveness of interactive multimedia on alternative energy materials to increase students' understanding of class III SD. This study uses the Research and Development method and the Borg and Gall development model. Trials at the development stage were carried out twice, namely small group trials and large group trials. Small group trials were carried out using 6 students with different intelligence criteria. Large group trials were conducted on all third grade students at SDN Totosan I with a total of 20 students. Research subjects in large group trials were selected using a random sampling technique. The research instrument consists of: (1) the validation instrument uses a validation sheet filled with two expert validators; (2) practical instruments using learning implementation sheets; (3) the effectiveness instrument uses test sheets and student response questionnaires. The results showed that the validity of alternative energy interactive multimedia obtained a validity percentage of 85% (very valid). The practicality of alternative energy interactive multimedia is 95% (practical). Effectiveness in terms of students' comprehension tests obtained and in terms of student responses obtained 90%, and in terms of student response questionnaires obtained 92% (very interesting), so that interactive multimedia is effectively used in learning.